Metode Transplantasi Padang Lamun Di Indonesia - I Gusti Ngurah Made Wiratama (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
One of the recoverable coastal resources that can make a high contribution to the coastal environment and to coastal communities is the seagrass ecosystem. Seagrass is a flowering aquatic plant that has the ability to adapt to live in the marine environment. Seagrass has many functions, such as a nursery ground, a feeding ground and a spawning ground for fish and other biota that have high economic value. Various threats to the sustainability of the seagrass ecosystem in Indonesia continue to increase year after year. Commonly used seagrass transplant methods include the plug, sprig, tie sack and frame method. Kawaroe et al., (2008) stated that the method that produced the highest seagrass yield was the plug method. Likewise, Lanuru et al., 2013 found that the plug method resulted in a better survival rate compared to the staple and frame method. The success of a transplant method is also largely determined by the characteristics of the substrate at the transplant site. According to Lanuru (2011), the sediment characteristics consisting of fine, muddy sand are better than coarse sand and less muddy as a substrate for Enhalus acoroides seagrass transplantation.